Akuntabilitas, Transparansi Pemerintah Desa dan Pengelolaan Dana Desa - Gwijangge, Nius; Jati, I Ketut; Asri Dwija Putri, I Gusti Ayu Made; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi; Vol 31 No 6 (2021), 2021)
This study aims to assess the accountability and transparency of the village government towards the management of the Village Fund in Sembiran village, Tejakula sub-district, Buleleng district. The sample used was 127 consisting of the village chief secretary of the village treasurer, the Village Consultative Body (BPD) as representatives of the community as well as section heads, with a probability sampling technique with the prorporotionate stratifid ramandom screening method. Data collection was carried out through distributing questionnaires. The analysis technique used in this study is a linear analysis of begada. The results showed that the management of village funds in the village was good enough to apply the principles and rules regarding the accountability of the transparency principle, and participation in village fund management was carried out both from the side of the village government and from the community side so that the accountability of the management of village funds would increase. Keywords:  Accountability; Transparency; Participation; Village Fund Management.